Modelo de avaliação de práticas de governança corporativa aplicado às empresas listadas na Bovespa - Sampaio, Márcia Suely Alves (2009)
The development and evolution of large corporations brought alterations into the corporate world, leading to the dilution of capital and, therefore, to the separation between ownership and management, a fact that triggered several conflicts which came to be called agency problems. The occurrence of corporate scandals led to discussions within international institutions and bodies about the issue of Corporate Governance (CG), and to the further publication of CG practice codes in several countries, the publication of OECD´s (Organization of Economic Cooperation and Development) Corporate Governance Principles in 1999, and the enactment of the Sarbanes-Oxley Act of 2002 in the United States. In Brazil, this trend got strengthened by the creation of the Brazilian Institute of Corporate Governance (IBGC), which elaborated the first version of the CG Best Practices Code in 1999, and by the initiatives of the regulatory bodies, such as the creation of the Differentiated CG Levels (NDGC) in 2000 by the Sao Paulo Stock Exchange (Bovespa); the elaboration of the CG Recommendations Chart, published in 2002 by the Securities Commission (CVM); the amendments to Act 6404/76, and others. All of them were aimed to meet the market´s demand for transparency and credibility. Some studies (La Porta, 1998; Silveira, 2005; Santos, 2000; Leal; Carvalhal, 2005) verified that the adoption of the CG Best Practices by the companies resulted in a better access to credit, less capital costs, better performance, lower risks and a more favorable attitude from every stakeholder. This study investigates, in sight of the significance of CG, the aspects to be considered when evaluating the CG practices implemented by a company in order to check their level of utilization. The general goal of this research was to present an evaluation model of the level of utilization of CG good practices by the companies traded in the Bovespa, based on the different categories established by domestic and international principles, codes and practices. This is an exploratory and descriptive research with regard to its goals, and a qualitative one with regard to the approach to the problem. Bibliographic and documentary methods were used, along with a field study having as subjects the public companies traded at the NDGC, levels 1 and 2, in the New Market and the Traditional Sao Paulo Stock Exchange, through the application of a structured questionnaire according to the defined CG evaluation model. One of the main results is that there is a gap between the level of use of corporate governance practices between companies subject to the regulations of the differentiated segments and of the New Stock Exchange and those used by the organizations traded at the Bovespa Traditional Exchange in the following parameters: Ownership, Executive Management, and Control. The companies belonging to the Traditional Stock Exchange must adhere in a stronger fashion to the good practices related mainly to the protection of shareholders, management quality, fiscal committee and to the setting of mechanisms for the resolution of conflicts of interest.